Raising local standards of infection control in Cameroon - Gobte, Nkwan Jacob (International Journal of Infection Control, 2008)
The team at Banso Baptist Hospital in Cameroon has introduced a number of improvements in local infection control standards and has succeeded in creating a safer and more conducive environment for staff and patients. Greater team spirit and persistent efforts have helped raise housekeeping standards and cleaning has become a regular feature across the hospital. The introduction of a sharps and waste disposal system has resulted in the reduction of needle-stick injuries among staff.